2019
DOI: 10.1097/prs.0000000000005091
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Lymphatic Dysfunction Amplifies the Negative Effects of Lymphatic Injury

Abstract: Background: Genetic mutations and obesity increase the risk of secondary lymphedema, suggesting that impaired lymphatic function prior to surgical injury may contribute to disease pathophysiology. Previous studies show that obesity not only decreases lymphatic function, but also markedly increases pathologic changes, such as swelling, fibroadipose deposition, and inflammation. However, although these reports provide circumstantial evidence supporting the hypothesis that baseline lymphatic defects amplify the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Furthermore, several studies show that obesity is a well-recognized risk factor and body mass index (BMI) has a direct correlation with development of spontaneous as well as secondary lymphedema following lymph node dissection for cancer treatment (Swenson et al, 2009;Greene et al, 2012;Greene and Maclellan, 2013;Mehrara and Greene, 2014;Maclellan et al, 2017). This is supported and likely related to the fact that baseline lymphatic function is a predictor of lymphedema development and severity of disease (Hespe et al, 2019). As a result, obese patients are 2to 3-fold more likely to develop lymphedema after surgery (Clark et al, 2005;Arrault and Vignes, 2006;Helyer et al, 2010).…”
Section: Obesity Causes Lymphatic Dysfunction and Increases Risk Of Lmentioning
confidence: 99%
“…Furthermore, several studies show that obesity is a well-recognized risk factor and body mass index (BMI) has a direct correlation with development of spontaneous as well as secondary lymphedema following lymph node dissection for cancer treatment (Swenson et al, 2009;Greene et al, 2012;Greene and Maclellan, 2013;Mehrara and Greene, 2014;Maclellan et al, 2017). This is supported and likely related to the fact that baseline lymphatic function is a predictor of lymphedema development and severity of disease (Hespe et al, 2019). As a result, obese patients are 2to 3-fold more likely to develop lymphedema after surgery (Clark et al, 2005;Arrault and Vignes, 2006;Helyer et al, 2010).…”
Section: Obesity Causes Lymphatic Dysfunction and Increases Risk Of Lmentioning
confidence: 99%
“…31 These outcomes should be viewed in light of the advanced disease burden in all patients (stage III or IV) and the high incidence of obesity, with 36 percent of patients having a body mass index greater than or equal to 30 kg/m 2 and 16 percent with a body mass index greater than or equal to 35 kg/m 2 . 32 When comparing patients that underwent dual-level compared with single-level transfer, the results were not significantly different at 12 months postoperatively. The reason for this is likely that patients selected for dual-level transfer had a more severe clinical lymphedema presentation, with uniform involvement of the entire upper extremity.…”
Section: Discussionmentioning
confidence: 87%
“…31 These outcomes should be viewed in light of the advanced disease burden in all patients (stage III or IV) and the high incidence of obesity, with 36 percent of patients having a body mass index greater than or equal to 30 kg/m 2 and 16 percent with a body mass index greater than or equal to 35 kg/m 2 . 32…”
Section: Discussionmentioning
confidence: 99%
“…The literature search yielded 2559 studies; 37 studies were found eligible and included for analysis (Baik et al, 2022; Bramos et al, 2016; Bucan et al, 2020; Bucan et al, 2022; Cho et al, 2017; Dai et al, 2016; Dai et al, 2020; Daneshgaran et al, 2020; Frueh et al, 2016; Frueh et al, 2022; García Nores et al, 2018; Gardenier et al, 2017; Hayashida et al, 2017; Hespe et al, 2019; Huang et al, 2016; Hwang et al, 2011; Iwasaki et al, 2017; Jørgensen et al, 2018; Jun et al, 2017; Kim et al, 2013; Komatsu et al, 2017; Kwon et al, 2019; Lee, Kang, et al, 2016; Lee, Song, et al, 2016; Ly et al, 2019; Nakajima et al, 2018; Oashi et al, 2012; Oashi et al, 2013; Ogino et al, 2020; Park et al, 2013; Roh et al, 2020; Roh, Cho, et al, 2017; Roh, Kim, et al, 2017; Shioya et al, 2016; Wang et al, 2020; Wiinholt et al, 2019; Yoshida et al, 2015) The PRISMA diagram of the literature search with included and excluded studies is shown in Figure 2. The study characteristics and quality assessment are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%